Technological Opportunities and New Firm Creation - Shane, Scott (Management Science, 2001)
Research on the creation of new high-technology companies has typically focused either on industry-level factors such as market structure and technology regime or on individual-level factors such as the work experience of entrepreneurs. This study complements these approaches by examining the effect of technological opportunities on firm formation. In particular, the study shows that the probability that an invention will be commercialized through firm formation is influenced by its importance, radicalness, and patent scope.